Dictionaries in foreign language learning - Ljubičić Gordana M. (University of Kragujevac - Faculty of Pedagogy, Užice, 2017)
Although many things concerning foreign language dictionaries have already been said and discussed in scientific papers, we can still add some facts that seem important at this moment. The main thing is the appearance of online dictionaries which are taking place of the print ones. The paper discusses the types of dictionaries and how their definitions have changed over time, compares the advantages and disadvantages of monolingual and bilingual dictionaries, as well as the print and online ones, and says something about the situation in our country as far as the dictionaries are concerned.